Observed data and WRF model output for Typhoon Longwang (2005) - Yuanlong Li (PANGAEA, 2019)
Observed data, i.e., station precipitation and radar reflectivity and WRF model output.
Supplement to: Li, Yuanlong; Lin, Yanluan; Wang, Yuqing (2019): A Numerical Study on the Formation and Maintenance of a Long-Lived Rainband in Typhoon Longwang (2005). Journal of Geophysical Research: Atmospheres, 124(19), 10401-10426, https://doi.org/10.1029/2019JD030600